The Role of MOOCs in Lifelong Learning and Professional Development - Wardhani, Rizky; Aziz, Safiullah; Khan, Jamil; Siswanty, Fitri (Journal International Inspire Education Technology, 2024)
Massive Open Online Courses (MOOCs) have emerged as a key tool for promoting lifelong learning and professional development in the digital age. As technology continues to evolve, individuals and professionals alike are seeking flexible, accessible educational opportunities to advance their skills and knowledge. MOOCs provide an affordable and scalable solution, allowing learners to engage with high-quality content from institutions worldwide. However, the effectiveness of MOOCs in supporting lifelong learning and professional growth remains underexplored. This study aims to evaluate the role of MOOCs in facilitating lifelong learning and enhancing professional development outcomes. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews with 300 participants who have completed MOOCs across various disciplines. The study focuses on participants’ motivations, experiences, and the perceived impact of MOOCs on their personal and professional growth. Data were analyzed using statistical techniques to identify patterns and thematic analysis to gain deeper insights into learner experiences. The results indicate that MOOCs play a significant role in promoting self-directed learning, with 80% of respondents reporting that MOOCs contributed to their personal knowledge and skill development. Additionally, 60% of participants highlighted that completing MOOCs led to career advancements or improved job performance. However, barriers such as completion rates and lack of personalized feedback remain challenges for maximizing the impact of MOOCs. In conclusion, MOOCs offer substantial benefits for lifelong learning and professional development, particularly in terms of accessibility and flexibility. To fully harness their potential, improvements in course design and support mechanisms are necessary to increase completion rates and learner engagement.